2017
DOI: 10.7454/jpdi.v1i1.34
|View full text |Cite
|
Sign up to set email alerts
|

Peran Tindakan Revaskularisasi terhadap Kesintasan Pasien Non ST Elevation Myocardial Infarction (NSTEMI)

Abstract: Pendahuluan. Pengaruh revaskularisasi terhadap kesintasan pasien non ST elevation myocardial infarction (NSTEMI) masih belum jelas. Waktu revaskularisasi yang optimal pada pasien NSTEMI belum ditemukan. Penelitian ini bertujuan mengetahui pengaruh revaskularisasi terhadap kesintasan pasien NSTEMI, juga mengetahui pengaruh waktu revaskularisasi terhadap kesintasan pasien NSTEMI.Metode. Penelitian dengan disain kohort retrospektif dilakukan terhadap 300 pasien non ST elevation myocardial infarction yang dirawat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…DM wasalso associated with higher rates of obesity, hypertension and hyperlipidemia. Bad lesions that occur are associated with risk factors such as DM, dyslipidemia, and decreased kidney function [11]. Another study showed there are The result of this study showed that DMwas associated with vascular stenosis, but not dyslipidemia and hypertension.…”
Section: Dm and Vessel Stenosismentioning
confidence: 58%
See 2 more Smart Citations
“…DM wasalso associated with higher rates of obesity, hypertension and hyperlipidemia. Bad lesions that occur are associated with risk factors such as DM, dyslipidemia, and decreased kidney function [11]. Another study showed there are The result of this study showed that DMwas associated with vascular stenosis, but not dyslipidemia and hypertension.…”
Section: Dm and Vessel Stenosismentioning
confidence: 58%
“…The age factor is related to the prevalence of coronary artery disease (CAD) and is an independent predictor of side effects after acute coronary syndrome (ACS) [7]. ACS can occur at a younger age but is rarely accompanied by comorbidities, so the coronary lesions experienced tend not to be extensive and complex [11]. In this study, most respondents were over 45 years old, 26.7% in the two or more vessel stenosis category, and 56.2% in the less than two vessel stenosis category.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation